2020
DOI: 10.1113/jp279779
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐day dependent effects of contractile activity on the phase of the skeletal muscle clock

Abstract: Key points Disruptions in circadian rhythms across an organism are associated with negative health outcomes, such as cardiometabolic and neurodegenerative diseases. Exercise has been proposed as a time cue for the circadian clock in rodents and humans. In this study, we assessed the effect of a single bout of endurance exercise on the skeletal muscle clock in vivo and a bout of muscle contractions in vitro. Timing of exercise or contractions influences the directional response of the muscle clock phase in viv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 82 publications
1
40
2
Order By: Relevance
“…The recently published work by Kemler et al . (2020) now provides clear evidence that exercise can also be considered a potent zeitgeber. Using both in vivo and in vitro models, they eloquently demonstrate that exercise elicits specific time‐of‐day effects on circadian rhythms and the core molecular clock machinery in skeletal muscle.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The recently published work by Kemler et al . (2020) now provides clear evidence that exercise can also be considered a potent zeitgeber. Using both in vivo and in vitro models, they eloquently demonstrate that exercise elicits specific time‐of‐day effects on circadian rhythms and the core molecular clock machinery in skeletal muscle.…”
mentioning
confidence: 99%
“…While previous studies have shown that exercise training can influence the circadian phase, Kemler et al . (2020) are the first to report that a single exercise session can shift the circadian phase in a direction that is dependent on when the exercise is conducted. Given that several populations, including a significant portion of the workforce, are routinely exposed to risk factors for circadian misalignment, this work provides important insights that will enable further exploration into the potential therapeutic effects of exercise on circadian rhythmicity.…”
mentioning
confidence: 99%
See 3 more Smart Citations